The Struggle Over Race, Class, Nationality & Gender: Social Dynamics and United Front Politics in Carlos Bulosan’s America is in the Heart - San Juan Jr., Epifanio (Social Sciences and Development Review, 2020)
Deploying a historical-materialist perspective, this essay analyzes the intersection of various thematic strands in the text of Bulosan ‘s masterpiece, America is in the Heart. The result is that novel is not just an immigrant narrative of success, but an acute dramatic rending of the class-racial struggle of Filipinos for national self-determination translated into the united-front politics of the Depression and the years before World War II. This unorthodox interpretation challenges the hegemonic appraisal of the novel that sanitizes its radical politics.